Pengaruh Pemberian Bonus pada Tabungan Simaster Terhadap Keputusan Nasabah Menabung Di BMT Mandiri Sejahtera Cabang Kedungpring Lamongan - Atika Habibah; Khozainul Ulum (Journal of Islamic Banking, 2021)
Nowdays, Islamic banks compete each other to get new customers. Many new Islamic banks have risen recently. Some consider cause customers to choose the bank for saving their money. Furthermore, many factors cause customers to choose appropriate product’s bank that they really need. Bonus is a gift given by the bank for customers, as a result customer is interested and decide to choose a product called “savings of Simaster“ among other products. “savings of Simaster is the only one giving the bonus. The purpose of the study is to test the effect of bonus in “savings of Simaster” toward the decision’s customers to save their money in BMT Mandiri Sejahtera in kedungpring. Customer’s decision is as a variable dependent (Y) and bonus is as a variable independent (X). In validity test, all indicators from variable bonus (X) have result 0,222> R table. The result of variable bonus (X) is (0,878), (0,880), (0,889), (0,900), (0,896), (0,905), (0,917), (0,907), and then the result of variable the customer’s decision (Y) is (0,884), (0,875), (0,857), (0,846), (0,869), (0,860), (0,888), (0,894). The result of simple linier regression is 0,951 which positive, so that the conclusion is variable bonus (X) affects variable customer’s decision (Y).